The law of nations and natural law, 1625-1800 - Zurbuchen, Simone (Brill, 2019)
"The Law of Nations and Natural Law 1625-1800 offers innovative studies on the development of the law of nations after the Peace of Westphalia. This period was decisive for the origin and constitution of the discipline which eventually emancipated itself from natural law and became modern international law. A specialist on the law of nations in the Swiss context and on its major figure, Emer de Vattel, Simone Zurbuchen prompted scholars to explore the law of nations in various European contexts. The volume studies little known literature related to the law of nations as an academic discipline, offers novel interpretations of classics in the field, and deconstructs 'myths' associated with the law of nations in the Enlightenment"-- Provided by publisher.
Includes paper presented at the workshop "The Law of Nations and Natural Law: 1625-1850" (University of Lausanne, 5-6 November 2015). --Acknowledgements, Page vii.
Keywords: International law -- History -- 17th century -- Congresses.; International law -- History -- 187th century -- Congresses.; Natural law -- History -- 17th century -- Congresses.; Natural law -- History -- 18th century -- Congresses.; Droit international -- Histoire -- 17e siècle -- Congrès.; Droit naturel -- Histoire -- 17e siècle -- Congrès.; Droit naturel -- Histoire -- 18e siècle -- Congrès.; International law; Natural law; 1600-18699; Legal history; Electronic books.; proceedings (reports); Conference papers and proceedings; History; Conference papers and proceedings.; Actes de congrès.